2018
DOI: 10.1021/acssuschemeng.8b00031
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Immobilized Polymeric PBI Derivative: Productive, Portable, and Photocatalytic System for Heck Coupling

Abstract: Perylene bisimide (PBI) derivative 3 having thiophene moieties at the bay positions has been designed and synthesized which forms J-aggregates in aqueous media and these aggregates serve as reactors for the generation of Au NPs and themselves undergo oxidative polymerization through thiophene moieties to generate polymeric species 4. The as prepared polymeric species 4 and gold NPs generated supramolecular ensemble 4: Au NPs which serve as promising photocatalytic system for Heck and multifold Heck coupling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The interactions between Pd and the cellulose matrix were also studied by XPS measurement, and all the spectra had been calibrated with C 1s of 284.6 eV. Figure f shows that the signals corresponding to Pd 3d in cellulose/Pd (335.30, 337.18, 340.50, and 342.34 eV) had some visible shifts compared with the commercial nano-Pd (335.44, 337.06, 340.73, and 342.41 eV), which suggested the interactions between Pd and the polymer backbone . Moreover, the O 1s (Figure g) spectrum of the bare cellulose with a peak at 532.54 (O–C) shifted to 532.72 eV, after the loading of palladium, while the C 1s spectrum (Figure S3) changed hardly, further indicating the interactions between oxygen-containing groups and palladium (Figure h). ,, The newly appeared CO peak in the O 1s spectrum of the cellulose/Pd arose from the dehydration of hydroxyl groups during calcination, accordantly with the FT-IR data .…”
Section: Resultsmentioning
confidence: 99%
“…The interactions between Pd and the cellulose matrix were also studied by XPS measurement, and all the spectra had been calibrated with C 1s of 284.6 eV. Figure f shows that the signals corresponding to Pd 3d in cellulose/Pd (335.30, 337.18, 340.50, and 342.34 eV) had some visible shifts compared with the commercial nano-Pd (335.44, 337.06, 340.73, and 342.41 eV), which suggested the interactions between Pd and the polymer backbone . Moreover, the O 1s (Figure g) spectrum of the bare cellulose with a peak at 532.54 (O–C) shifted to 532.72 eV, after the loading of palladium, while the C 1s spectrum (Figure S3) changed hardly, further indicating the interactions between oxygen-containing groups and palladium (Figure h). ,, The newly appeared CO peak in the O 1s spectrum of the cellulose/Pd arose from the dehydration of hydroxyl groups during calcination, accordantly with the FT-IR data .…”
Section: Resultsmentioning
confidence: 99%
“…[48] Jie et al have reported a visible-light-driven atom transfer/radical addition of (phenylsulfonyl)difluoromethyl iodide to styrenes using Ru-(bpy) 3 Cl 2 ⋅ 6H 2 O and KH 2 PO 4 as the base to achieve various difluoromethylated molecules. [49] A cooperative photocatalysis involving the energy transfer from photoactivated CdS quantum dots to Pd-complex for Heck coupling of styrene and iodocyclohexane to yield 2-cyclohexylstyrene have been reported by Zhang et al [50] As predicted, the increasing popularity of heterogeneous photocatalysts for the Mizoroki-Heck cross-coupling has emerged as a prevalent technique in organic synthesis as shown by a large variety of photocatalyst materials such as Pd/ TiO 2 nanoparticles, [51] supramolecular HPÀ T@AuÀ Fe 3 O 4 , [52] PdCl 2 /TiO 2, [53] Au NPs via perylene bisimide, [54] Pd nanoparticles supported over carbon nano-coils (Pd/CNCs), [55] palladium (Pd) NPs, [56] Pd-rGO/CNT/CaFe 2 O 4 , [57] homoleptic-Ru-bis-terpy complexes, [58] AuPd@N-rich carbon nitride, [59] and mesoporous graphitic carbon nitride (mpg-CN). [60] Despite the extensive achievement of transition-metal-based photocatalysts, most of them acquire major weaknesses in terms of stability, reusability, toxicity, and more costs.…”
Section: Chemistryselectmentioning
confidence: 98%
“…As predicted, the increasing popularity of heterogeneous photocatalysts for the Mizoroki‐Heck cross‐coupling has emerged as a prevalent technique in organic synthesis as shown by a large variety of photocatalyst materials such as Pd/TiO 2 nanoparticles, [51] supramolecular HP−T@Au−Fe 3 O 4 , [52] PdCl 2 /TiO 2, [53] Au NPs via perylene bisimide, [54] Pd nanoparticles supported over carbon nano‐coils (Pd/CNCs), [55] palladium (Pd) NPs, [56] Pd‐rGO/CNT/CaFe 2 O 4 , [57] homoleptic‐Ru‐bis‐terpy complexes, [58] AuPd@N‐rich carbon nitride, [59] and mesoporous graphitic carbon nitride (mpg‐CN) [60] . Despite the extensive achievement of transition‐metal‐based photocatalysts, most of them acquire major weaknesses in terms of stability, reusability, toxicity, and more costs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the AuPd/g-C 3 N 4 nanohybrid showed a very high TOF of 7920 h −1 in the C-C cross-coupling reaction. Other researchers have used a variety of support materials such as semiconductors (e.g., CeO2, graphitic carbon nitride (g-C3N4)) [104,105], metal-organic frameworks (MOF, UiO-66-NH2) [106], polymers (e.g., perylene bisimide (PBI), polystyrene) [107,108], wide band gap semiconductors (TiO2) [109][110][111][112], and silica [113]. Semiconductors that have narrower band gaps than 3.1 eV (i.e., 2.7 eV for g-C3N4) can absorb visible light to generate electron-hole pairs, which are transferred to metal NPs.…”
Section: Aunp-assisted Plasmonic Photocatalysts For C-c Cross-couplingmentioning
confidence: 99%